Ed Taylor, father of migrant missions - Heath, Lou Mishler; Woodson, Jack (Nashville, Tenn. : Broadman Press, 1982)
A biography of a mill worker, who became a church pastor and eventually developed a ministry of migrant workers.
Keywords: Taylor, John Edward -- Juvenile literature; Taylor, John Edward; Baptists -- United States -- Clergy -- Biography -- Juvenile literature; Church work with migrant labor -- United States -- Juvenile literature; Clergy; Church work with migrant labor -- Baptists